Pengembangan sistem pengukuran dimensi kendaraan bermotor berbasis mikrokontroler - ARIEF NOVIANTO; Nanang Okta Widiandar Nanang Okta Widiandar; Syaibani Ikhsan Syaibani Ikhsan; Agus Siswono Agus Siswono (Universitas Muhammadiyah Metro, 2026)
This research is an improvement of the previous prototype. The objective of this research is to develop a dimension measurement system that is easier, faster, lighter, more accurate, and more portable. Research and Development (R&D) methods were used to develop a tool that is in line with the research objectives. This tool works by emitting infrared rays from a distance sensor laser, which are then reflected on a reflector on the reflector rod. The data is processed using an ESP32 microcontroller, and the measurement results can be viewed on an LCD screen and printed using a thermal printer. The LCD module includes options for measuring two- and three-axle vehicles. The device is made of aluminium, making it lighter. It is easy to fold, and to improve accuracy, a laser is installed to ensure that the emitter rod and reflector are perpendicular to each other. A comparison of the dimensional measurements between this measuring device and a calibrated tape measure shows a significance value (P) of 0.227. With a significance value greater than 0.05, the results are considered not significantly different from the calibrated tape measure but with an easier and faster process.